Photocatalytic dye degradation using novel Polypyrrole-Tungsten Oxide hybrid nanocomposite system. - Nandini Iyer; Jayant Kher; Shekhar Bhame (Journal of Water and Environmental Nanotechnology)
The present study features the synthesis of Dodecylbenzene sulphonic acid-doped polypyrrole tungsten oxide (PPy-WO3) nanocomposites and its photocatalyic studies on Methylene Blue (MB). The nanocomposites of PPy with a very low concentration of WO3 were prepared using 0.05 to 0.3 wt.%, of WO3 nanoparticles. The composites were characterized by using-ray Diffraction, FTIR and FESEM for phase identification, morphological studies. The electrical conduction of the nanostructured materials at room temperature exceeded that of PPy, with the electrical conductivity increasing linearly with higher WO3 concentrations. The band gap for the nanocomposite was found to be 2.12eV. The PL spectra substantiated the adequate segregation of charge carriers photoexcited in the samples. The nanocomposites were tested as photocatalysts for the degradation of methylene blue dye (MB). A two-step mechanism has been propsed for dye removal: adsorption (in the absence of UV light) and photodegradation on the photocatalyst surface (in the presence of UV light). The maximum removal efficiency for methylene blue dye was 98.31% in UV light for 0.16 g/L of the 0.3 wt.% PPy- WO3 nanocomposite, with a dye concentration of 5 mg/L. The addition of p-benzoquinone (*O2- scavenger) contributed to a significant decrease in the photodegradation efficiency of the catalyst, i.e.,63.21%, and thus can be believed as the main active species for the degradation of the methylene blue dye.